2008
DOI: 10.1161/circheartfailure.107.740704
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Oral Direct Renin Inhibitor Aliskiren in Patients With Symptomatic Heart Failure

Abstract: Addition of aliskiren to an ACE inhibitor (or angiotensin receptor blocker) and beta-blocker had favorable neurohumoral effects in heart failure and appeared to be well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
248
1
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 339 publications
(263 citation statements)
references
References 35 publications
4
248
1
10
Order By: Relevance
“…Preliminary studies suggest that it may also prove to be effective in treatment of heart failure [29]. The observation that it has additive effects to ACE inhibitor or ARB dosing [30] is consistent with prior studies suggesting additive benefits when an ARB is added to an ACE inhibitor.…”
Section: R I a I A Ii At R At R Aldsupporting
confidence: 75%
“…Preliminary studies suggest that it may also prove to be effective in treatment of heart failure [29]. The observation that it has additive effects to ACE inhibitor or ARB dosing [30] is consistent with prior studies suggesting additive benefits when an ARB is added to an ACE inhibitor.…”
Section: R I a I A Ii At R At R Aldsupporting
confidence: 75%
“…The Aliskiren Observation of Heart Failure Treatment (ALOFT) study demonstrated that aliskiren decreased BNP in heart failure patients not by a BP-lowering effect but possibly by increased natriuresis. 22 Westermann et al 23 reported that aliskiren improved cardiac function and remodeling after myocardial infarction by normalization of intracellular signaling stimulated by AT II without altering BP in an animal model. Imanishi et al 24 reported that aliskiren improved vascular endothelial function and protected against atherosclerosis by impaired nitric oxide bioavailability and decreased inflammatory mediators without altering BP in an animal model.…”
Section: Discussionmentioning
confidence: 99%
“…No estudo ALOFT, o alisquireno reduziu as concentrações de NT-pro-BNP e excreção de aldosterona 315 . No estudo ASPIRE, que incluiu pacientes com 2-8 semanas de infarto agudo do miocárdio com disfunção ventricular, não houve benefício quanto ao remodelamento ou eventos clínicos 316 .…”
Section: Inibidores Da Reninaunclassified